Islands of Shared Knowledge: Specialization and Mutual Understanding in Problem-Solving Teams - Postrel, Steven (Organization Science, 2002)
Where should the boundaries of knowledge between economic actors be located in order to maximize the efficiency of their interactions? In particular, what circumstances determine whether it makes sense for adjacent stages in the value chain to invest in the development of common understanding, and when does it make sense for them to operate in mutual ignorance? To address these questions, it is necessary to construct a kind of production function which takes different forms of knowledge—specialist capability and trans-specialist understanding—as inputs and relates them to problem-solving output. Using a simple model of product design as a template, it is possible to derive such a production function. One can then use its properties in conjunction with plausible assumptions about the cost of acquiring different kinds of knowledge to develop general principles that explain when efficiency requires costly learning across specialties and when it is better to allow specialties to operate in mutual ignorance of one another's domains. The derived production function, contrary to some intuition and previous literature, implies that specialist capability can substitute for knowledge shared across specialties. This result in turn implies that the nature of learning costs, rather than the shape of knowledge benefits, plays the predominant role in determining when mutual ignorance is a good idea. The analysis also helps resolve the following paradox: The economy depends for its efficiency upon a drastic separation of knowledge across individuals and organizational units, yet studies of product development find that greater knowledge commonality is associated with better firm performance. An implication of the substitutability of specialized and trans-specialty knowledge is that situations where learning across specialties is desirable seem relatively rare in the economy as a whole. These situations are disproportionately common, however, in those areas where important managerial activity takes place. A key role of management is to attend to the strategic, operational, and governance needs of these “islands of shared knowledge in a sea of mutual ignorance.”